Assessment of Long-Term Effects of Sports-Related Concussions: Biological Mechanisms and Exosomal Biomarkers - Ledreux, Aurélie; Pryhoda, Moira K.; Gorgens, Kim; Shelburne, Kevin; Gilmore, Anah; Linseman, Daniel A.; Fleming, Holly; Koza, Lilia A.; Campbell, Julie; Wolff, Adam; Kelly, James P.; Margittai, Martin; et al. (Frontiers in Neuroscience, 2020)
Concussion or mild traumatic brain injury (mTBI) in athletes can cause persistent symptoms, known as post-concussion syndrome (PCS), and repeated injuries may increase the long-term risk for an athlete to develop neurodegenerative diseases such as chronic traumatic encephalopathy (CTE) and Alzheimer’s disease (AD). The Center for Disease Control estimates that up to 3.8 million sport-related mTBI are reported each year in the US. Despite the magnitude of the phenomenon, there is a current lack of comprehensive prognostic indicators and research has shown that available monitoring tools are moderately sensitive to short-term concussion effects but less sensitive to long-term consequences. The overall aim of this review is to discuss novel, quantitative, and objective measurements that can predict long-term outcomes following repeated sports-related mTBIs. The specific objectives were 1) to provide an overview of the current clinical and biomechanical tools available to health practitioners to ensure recovery after mTBIs, 2) to synthesize potential biological mechanisms in animal models underlying the long-term adverse consequences of mTBIs, 3) to discuss the possible link between repeated mTBI and neurodegenerative diseases and, 4) to discuss the current knowledge about fluid biomarkers for mTBIs with a focus on novel exosomal biomarkers. The conclusions from this review are that current post-concussion clinical tests are not sufficiently sensitive to injury and do not accurately quantify post-concussion alterations associated with repeated mTBIs. In the current review, it is proposed that current practices should be amended to include a repeated symptom inventory, a cognitive assessment of executive function and impulse control, an instrumented assessment of balance, vestibulo-ocular assessments and an improved panel of blood or exosome biomarkers.